2009
DOI: 10.1016/j.bcp.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Opiates inhibit paclitaxel uptake by P-glycoprotein in preparations of human placental inside-out vesicles

Abstract: The use of either methadone or buprenorphine for treatment of the pregnant opiate dependent patient improves maternal and neonatal outcome. However, patient outcomes are often complicated by neonatal abstinence syndrome (NAS). The incidence and severity of NAS should depend on opiate concentration in the fetal circulation. Efflux transporters expressed in human placental brush border membranes decrease fetal exposure to medications by their extrusion to the maternal circulation. Accordingly, the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Besides, it could also be suggested that maraviroc inductive properties toward ABCC2 could counterbalance ABCC2 rather low placental expression (28). Regarding ABCB1, one hypothesis that could partly explain the lack of correlation we observed could be the variability of frequency between ethnic groups of the 3435C¡T substitution, which has been associated with a decrease of ABCB1 mRNA and protein expression (33,34). Indeed, in European Caucasians, 3435T frequencies of 0.52 to 0.57 were reported, whereas in Africa, the prevalence is much lower, 0.17 to 0.27 (35,36).…”
Section: Discussionmentioning
confidence: 88%
“…Besides, it could also be suggested that maraviroc inductive properties toward ABCC2 could counterbalance ABCC2 rather low placental expression (28). Regarding ABCB1, one hypothesis that could partly explain the lack of correlation we observed could be the variability of frequency between ethnic groups of the 3435C¡T substitution, which has been associated with a decrease of ABCB1 mRNA and protein expression (33,34). Indeed, in European Caucasians, 3435T frequencies of 0.52 to 0.57 were reported, whereas in Africa, the prevalence is much lower, 0.17 to 0.27 (35,36).…”
Section: Discussionmentioning
confidence: 88%
“…Figure 3 shows that encapsulation of digoxin in nanoparticles resulted in an increase in the apparent permeability of the drug in the apical (maternal) to basolateral (fetal) direction by 2.5-fold (p < 0.05). The transport studies were repeated in the presence of 100 μM verapamil, a P-gp inhibitor [16]. The concentration of verapamil selected for this study matches the concentration used by Polachek et al as an inhibitor of P-gp in BeWo cells [32].…”
Section: Transport Studiesmentioning
confidence: 99%
“…The transport of digoxin as free drug or encapsulated in nanoparticles was compared using the BeWo b30 cell line, an in vitro model of human placental t rophoblast cells separating the maternal and fetal circulations [15]. Finally, the effect of nanoencapsulation on the interaction of digoxin with P-gp was investigated by means of transport studies in the presence of verapamil, a P-gp inhibitor [16].…”
Section: Introductionmentioning
confidence: 99%
“…The same group demonstrated that methadone transfer was significantly higher in the fetal-tomaternal direction, likely due to the unidirectional activity of P-gp (142). Methadone was also shown to inhibit the transfer of paclitaxel in human placental inside-out vesicles, demonstrating a greater affinity for P-gp than the classic inhibitor verapamil (143). Similarly, methadone was shown to stimulate P-gp activity at higher concentrations (100 μM), and Caco-2 monolayer transport studies demonstrated that verapamil and GF120918 significantly reduced methadone efflux (111).…”
Section: Methadonementioning
confidence: 88%